Characterization and analysis of Ki-67-immunoreactivity in brain astrocytoma. - Shpon‘ka, I. S.; Shynkarenko, T. V.; Poslavska, O. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. A significant problem of brain tumors diagnostics is the subjective histological criteria. A promising area of research is estimation of mitotic activity level, but counting mitotic figures can not be accurate in slides stained by hematoxylin and eosin and therefore immunohistochemical detection of expression Ki-67 is widely used. Despite considerable experience in using proliferative index, determined by using Ki-67-immunoreactivity, the technique requires further research for standardization and optimization. Objective. To determine the diagnostic value of the Ki-67 expression in astrocytomas. Methods. The study included 45 astrocytomas, which were received by biopsy or operation. Imunohistochemical determining of Ki-67-labeling was used for calculating of proliferation index. Statistical analysis was performed by nonparametric tests. Results. It was observed similar and relatively low levels of Ki-67 expression in astrocytoma Grade I and II (WHO), significantly lower than in groups III and IV levels. It was revealed significant differences between the results obtained by different researchers. Conclusion. The level of Ki-67 expression correlates with Grade of astrocytomas (p <0,05). Great overlaps of Ki-67 expression (between I and II, III and IV level) does not allow its use in the differentiation of Grades. Despite the strong statistically significant relationship (p <0,05) between the results obtained by different researchers, a significant difference between them requires consideration when comparing with other data.